Students’ perception on existing facilities for physically challenged students in higher education institution: a comparative study on Khulna University and govt. BL College, Khulna (Research in Agriculture Livestock and Fisheries, 2024)
Extra facilities are essential to the success of physically challenged students in higher education. In a study of 67 general and 13 physically challenged students of Khulna University and Govt. BL College, Khulna, the participant responded to interviews on existing facilities for physically challenged students in higher education institutions. This study also compares inequalities among physically challenged and general students. Findings show that physically challenged students can achieve success in higher education through special facilities. To ensure human rights for all and to develop human resources through an educated workforce, inclusive education is must for physically challenged students. Higher education is considered as a way to gain much knowledge where the institution's environment plays an important role in the amplification of knowledge. The study obtained students' perception of existing facilities for physically challenged students in higher education institutions and essential measures that should be taken to make them human resources. Students indicated that teachers' and friends' attitudes are satisfied in both two institutions but, a little more concern for administrative authority is needed for environmental and service facilities as well as inclusive education.Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 61-67.